2019
DOI: 10.1049/iet-ipr.2019.0667
|View full text |Cite
|
Sign up to set email alerts
|

Image encryption algorithm based on image hashing, improved chaotic mapping and DNA coding

Abstract: In order to improve the problems of security and robustness for existing image encryption algorithms and to reduce the security risks of encryption algorithms against statistical analysis, differential attacks, exhaustive attacks, cropping and noise attacks etc., a novel image encryption algorithm based on image hashing, improved chaotic mapping and DNA coding is proposed. Firstly, extracting the image features and evenly block after pre‐processing the original image and fingerprint image. Secondly, the featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Improved CS Algorithm. Chaotic mapping [30][31][32] is the inherent characteristic of nonlinear dynamical system, which is a kind of random process with the certainty of the regular expression. erefore, it is often used to improve the performance of intelligent algorithms to find the best performance.…”
Section: Basic Cs Algorithmmentioning
confidence: 99%
“…Improved CS Algorithm. Chaotic mapping [30][31][32] is the inherent characteristic of nonlinear dynamical system, which is a kind of random process with the certainty of the regular expression. erefore, it is often used to improve the performance of intelligent algorithms to find the best performance.…”
Section: Basic Cs Algorithmmentioning
confidence: 99%
“…Thus, it matches the demand for image encryption [35]. Recent works found that combining DNA encoding and chaos is an efficient and secure scheme but is still vulnerable to common attacks when the key space is not large enough, not unique, unchanged, or independent from the input data [17, 21, 26, 36–47]. Ur Rehman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it matches the demand for image encryption [35]. Recent works found that combining DNA encoding and chaos is an efficient and secure scheme but is still vulnerable to common attacks when the key space is not large enough, not unique, unchanged, or independent from the input data [17,21,26,[36][37][38][39][40][41][42][43][44][45][46][47]. Ur Rehman et al suggested a selective block cipher encryption algorithm based on DNA sequence and Piece Wise Linear Chaotic Map (PWLCM) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shortcomings of traditional electronic computer such as small storage capacity and serial connection, the combination of DNA and computer technology is a hot spot in cryptography research [ 5 ]. In recent years, researchers use computers instead of traditional biochemical experiments to achieve DNA manipulation, which is called pseudo-DNA manipulation [ 19 , 20 ]. The DNA molecule has the characteristics of large storage capacity and strong parallelism [ 21 , 22 ], which can be well applied to the image encryption field with huge amount of information and high real-time requirements, including DNA encoding [ 23 ], DNA computing [ 24 ] and DNA decoding [ 25 ] etc.…”
Section: Introductionmentioning
confidence: 99%